STATUS GIZI BALITA BERBASIS STATUS PEMILIH MAKAN DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU SEMARANG - Hapsari Sulistya Kusuma; Nura Ma’shumah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Introduction: Picky eater is the eating disorder which is characterized with several symptoms, there are; trouble eating, refusing to feed, and spewing the food. Picky eater which is continuously occurred on children effects on children nutritional status being a under nutritional. In work area of Kedungmundu Health Care Semarang, it is found under nutritional status on children for 1, 2% in 2007 year. The aim of this research is to identify the relation between picky eater and nutritional status on children in work area of Kedungmundu Health Care Semarang. Research Method: The design of this research is cross sectional with analytic research. The sampling are 68 childrens which systematic random sampling. It is found 41 childrens who are picky eater and 27 childrens who are non picky eater. Moreover, interviewer method is used to collect the data with questioners instrument. The picky eater categorized into two categories, picky eater and non picky eater. Children’s nutritional status determined by Weight for Height index. Statistical analysis, Mann Whitney test used to analyze the correlation between independent and dependent variable. Research Result: There is no correlation between picky eater status and the nutritional status (p 0,467 > 0, 05).Key Word: Picky Eater Status, Nutritional Status.